Peran Ruang Bersama terhadap Keterikatan Fungsional (Functional Attachment) di Rusunawa Mojosongo, Surakarta - Mohamad Muqoffa; Neni Nurul Rosalina (Universitas Sebelas Maret Surakarta, 2023)
This study focuses on the role of shared-space in the Rusunawa environment in creating functional attachment for residents in the Rusunawa Mojosongo. Functional attachment can occur when a person's needs are met in a setting of place. Place attachment can make a better quality of life. Shared-space as a public open space in the Rusunawa must be able to provide shared facilities that can meet the needs of the residents of the Rusunawa functionally. Uses & activities, access & linkage, green spaces existence, and their environmental response in the Shared-spaces are studied as aspects of Functional Engagement. Observations and interviews were conducted with Rusunawa residents who have lived since the inception of the Rusunawa, and how residents use the shared space for their daily activities. Result shows that shared space has a vital role in the neighborhood even in public housing to create the functional attachment as attempt to create attachment to the place.